Pharmacokinetics and Anticoagulant Effect of Hirudin in Man - Markwardt, F; Nowak, G; Stürzebecher, J; Grießbach, Uta; Walsmann, P; Vogel, G (Thrombosis and Haemostasis, 1984)
The pharmacokinetics and the effects on the haemostatic system of hirudin were assessed in six healthy subjects after single intravenous or subcutaneous dose (1000 AT-U/kg). When hirudin was given intravenously first-order elimination kinetics followed the initial distribution phase. The decline in plasma hirudin concentration was most adequately expressed by a biexponential equation describing a two compartment model. A mean elimination half-life of 0.84 hr and a mean volume of distribution of 12.9 1 were calculated. After subcutaneous injection a low hirudin level (∼0.5 AT-U/ml) was maintained for a prolonged period of time.In the 24 hour-urine up to 50 per cent of the administered amount of hirudin was excreted in active form.Thrombin time, partial thromboplastin time and prothrombin time measured in plasma samples ex vivo were prolonged dependent on the hirudin plasma level. Platelet counts, fibrinogen level and the fibrinolytic system were unchanged. Bleeding time was prolonged twice at maximum.Subcutaneous or intravenous administration of pure hirudin was tolerated without side-effects.
Keywords: Hirudin; Pharmacokinetics; Effect on haemostasis